PENGARUH FEMALE DIRECTOR DAN COR PENGARUH FEMALE DIRECTOR DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA PERUSAHAAN - aisah astiyani; Ani Fitrotunnisa; Erika Puspita Sari (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
The development of an increasingly competitive business world requires every company to be more careful in setting its strategy in order to continue to compete in the market. Corporate strategy plays an important role in maintaining competitive advantage. This study is intended to determine the effect of female directors and CSR on company performance. The theory used is the Agency and Stackholder Theory. We used multiple regression analysis method. The sample used in this study was 20 public sector mining companies for the 2017-2019 period in Indonesia. The results show that female directors and CSR have no effect on company performance.